FRI0082 Radiographic progression in rheumatoid arthritis in the 21st century. (23rd January 2014) - Gärtner, M.; Alasti, F.; Supp, G.; Smolen, J.; Aletaha, D.
Abstract : Background: Progression of joint damage as measured radiographically is a hallmark of rheumatoid arthritis (RA), and its reduction a key claim for traditional and novel antirheumatic drugs. Data from clinical trials may be interpreted to indicate that the observed progression of RA (in comparator groups of clinical trials) has decreased over the past two decades. 1 Although these observations mainly stem from clinical trials, it has been hypothesized that RA may have become a less destructive disease. Objectives: To evaluate the frequency as well as the level of radiographic progression in real life routine RA patients in the 21 st century. Methods: RA patients of our outpatient clinic, who had two x-rays performed over a three to five year interval between the years 2000 and 2012 were included. X-rays of the hands and feet were scored according to the Sharp van der Heijde (SvdH; range 0-448) method. 2 Clinical and demographic data were collected from the patients' charts. Disease activity was assessed using the clinical disease activity index (CDAI-average over time). Patients were separated into three periods of time (2000-2004, 2005-2008, 2009-2012) and the annual radiographic progression was calculated based on the observed progression in these periods. The mean number of joints with radiographic progression per patient, as well as the mean grade of progression per joint (erosion/joint space narrowing, JSN) were evaluated. Lack of progression was defined as no progression in total SvdH. Results: Of the 444 patients included (mean duration of RA 7.4±9.4 years, 56.2% rheumatoid factor positive, 62.0% ACPA positive), 406 (91.4%) showed radiographic progression over a mean of 3.8±0.6 years. In all progressors we found no difference in rates of total radiographic progression, erosion score, or JSN, the three different time periods (Table 1 ). Conclusions: Only a minority of patients did not progress structurally over three to five years. The temporal trend analysis indicates that on the background of similar average disease activity and mixed treatment, the overall annual progression was constant during the last decade. However, in general progression of joint damage was low. References: Rahman MU et al. Ann Rheum Dis 2011; 70(9):1631-1640. van der Heijde D. J Rheumatol 1999; 26(3):743-745. Disclosure of Interest: None Declared